Crowdlicit: A System for Conducting Distributed End-User Elicitation and Identification Studies - Ali, Abdullah X.; Morris, Meredith Ringel; Wobbrock, Jacob O. (CHI 2019, 2019)
End-user elicitation studies are a popular design method. Currently, such studies are usually confined to a lab, limiting the number and diversity of participants, and therefore the representativeness of their results. Furthermore, the quality of the results from such studies generally lacks any formal means of evaluation. In this paper, we address some of the limitations of elicitation studies through the creation of the Crowdlicit system along with the introduction of end-user identification studies, which are the reverse of elicitation studies. Crowdlicit is a new web-based system that enables researchers to conduct online and in-lab elicitation and identification studies. We used Crowdlicit to run a crowd-powered elicitation study based on Morris’s “Web on the Wall” study (2012) with 78 participants, arriving at a set of symbols that included six new symbols different from Morris’s. We evaluated the effectiveness of 49 symbols (43 from Morris and six from Crowdlicit) by conducting a crowd-powered identification study. We show that the Crowdlicit elicitation study resulted in a set of symbols that was significantly more identifiable than Morris’s.